1993
DOI: 10.1089/ard.1993.3.53
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cellular Binding and Uptake of Antisense Phosphodiester, Phosphorothioate, and Mixed Phosphorothioate and Methylphosphonate Oligonucleotides

Abstract: The effects of phosphorothioate (S-oligonucleotide) or terminal phosphorothioate-phosphodiester (S-O-oligonucleotides) or methylphosphonate-phosphodiester (MP-O-oligonucleotides) modifications on mouse spleen cell surface binding, uptake, and degradation were studied using fluorescein (FITC)-conjugated oligonucleotides. S-oligonucleotides had the highest cell binding and uptake, followed by S-O-, O-, and MP-O-oligonucleotides. Competition studies indicated that S-oligonucleotides have an increased affinity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(119 citation statements)
references
References 14 publications
9
110
0
Order By: Relevance
“…The presence of unmethylated CpG motifs, however, appears unnecessary for stimulation of neutrophil functions, as a similar degree of activation was observed using S-ODN containing or lacking these motifs. Although the half-life of P-ODN in culture is estimated at 4 h, while that of S-ODN is 14 h [37,38], it seems unlikely that differences in the stimulatory potential of the two classes of ODN could be attributed to a higher rate of P-ODN degradation; we assessed responses within a 30 min incubation period. Our observations that S-ODN stimulates neutrophil functions are also in agreement with Bylund et al [36], who found that S-ODN induce neutrophil NADPH-oxidase activation, leading to the release of reactive oxygen species, degranulation, and L-selectin shedding in a CpG-independent but phosphorothioatedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of unmethylated CpG motifs, however, appears unnecessary for stimulation of neutrophil functions, as a similar degree of activation was observed using S-ODN containing or lacking these motifs. Although the half-life of P-ODN in culture is estimated at 4 h, while that of S-ODN is 14 h [37,38], it seems unlikely that differences in the stimulatory potential of the two classes of ODN could be attributed to a higher rate of P-ODN degradation; we assessed responses within a 30 min incubation period. Our observations that S-ODN stimulates neutrophil functions are also in agreement with Bylund et al [36], who found that S-ODN induce neutrophil NADPH-oxidase activation, leading to the release of reactive oxygen species, degranulation, and L-selectin shedding in a CpG-independent but phosphorothioatedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been demonstrated to be useful for studying and comparing the uptake and intracellular localization of different oligonucleotides conjugated to fluorescent molecules such as fluorescein [26]. Oligonucleotide uptake in cell lines has previously been shown to be saturable, sequence independent, and temperature and energy dependent [27].…”
Section: -(Thymidinmentioning
confidence: 99%
“…Most of the researchers have focused on the cellular activating effect of the signal transduction events that are triggered by TLR9 ligation while less is known about the modulation of antigen uptake by CpG ODN. Some authors mentioned the relevance of 'stickiness' of synthetic ODNs [6,7] that can take part in the uptake of antigen and thus have an impact on the elicited immune response. There is evidence that ligation of CpG to a particulate antigen can enhance the uptake of CpG via endocytosis initiated by the antigen-specific BCR [8].…”
Section: Introduction 54mentioning
confidence: 99%